(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Trace element imbalance in the body is an important factor affecting human health. A deficiency or excess of trace elements such as iron, zinc, magnesium, and copper can lead to serious consequences, including anemia, immune system disorders, and chronic diseases. This article examines the key aspects of the influence of trace elements on the body, modern laboratory diagnostic methods such as atomic absorption spectrometry, mass spectrometry, and biochemical tests, as well as the results of current studies. Particular attention is paid to the integration of innovative technologies for accurate detection of disorders.